I know that $\sum_{k=1}^\infty|y_n|^2=S<\infty$. I also have that $\lambda >1$.

I need to show that $$ \sum_{k=1}^\infty \left| \frac{y_1}{\lambda^k} + \frac{y_2}{\lambda^{k-1}} + \cdots \frac{y_k}{\lambda} \right|^2 $$ converges. (When $k=1$, there is one term in absolute value, when k=2, there are two terms etc...) Can someone please help?

I tried using https://en.wikipedia.org/wiki/Minkowski_inequality:

If I can show that $$ \sum_{k=1}^N \left| \frac{y_1}{\lambda^k} +\frac{y_2}{\lambda^{k-1}} +\cdots \frac{y_k}{\lambda}\right|^2 $$ is bounded for any N, I am done.

By Minowski's inequality:

$$ \begin{split} \sum_{k=1}^N \left| \frac{y_1}{\lambda^k} +\frac{y_2}{\lambda^{k-1}} +\cdots \frac{y_k}{\lambda}\right|^2 &= \left[ \left( \sum_{k=1}^N \left| \frac{y_1}{\lambda^k} +\frac{y_2}{\lambda^{k-1}} +\cdots \frac{y_k}{\lambda} \right|^2 \right)^{1/2} \right]^2 \\ &\le \left[ \left(\sum_{k=1}^N \frac{|y_1|^2}{\lambda^{2k}}\right)^{1/2} +\left(\sum_{k=2}^N \frac{|y_2|^2}{\lambda^{2k-2}}\right)^{1/2} +\cdots + \left(\frac{|y_n|^2}{\lambda^2}\right)^{1/2} \right]^2. \end{split} $$

Now since $\lambda > 1$ we have a geometric series in each part, so we take each $|y_i|^2$ out of the sum, and then each sum is bounded:

$$\ldots \le \left[K|y_1|+K|y_2|+\cdots+K|y_N|\right]^2 =\left[K \sum_{k=1}^N|y_k| \right]^2.$$

However, I do not know that $\sum_{k=1}^N|y_k|$ is bounded for any $N$? And the problem with $[\sum_{k=1}^N|y_k|]^2$ is that it contains many cross-terms, it contains $\sum_{k=1}^N |y_k|^2$, but also many more cross-terms.

Any tips?


We need to prove that $$ \sum_{k=1}^\infty\left|\sum_{j=1}^ky_j\left(\frac{1}{\lambda}\right)^{k-j}\right|^2\frac{1}{\lambda^2}<+\infty. $$

  1. Denote $x_k=\sum_{j=1}^ky_j\left(\frac{1}{\lambda}\right)^{k-j}$, which gives $$ x_{k+1}=\frac{1}{\lambda}x_k+y_{k+1}, \qquad x_0=0,\ k\ge 0.\tag1 $$
  2. Do $z$-transform of the equation, i.e. multiply by $z^{k+1}$ and sum up. With the notations $$ x(z)=\sum_{k=0}^\infty x_k z^k,\qquad y(z)=\sum_{k=0}^\infty y_k z^k $$ we get $$ x(z)=\frac{z}{\lambda}x(z)+y(z)\qquad\Leftrightarrow\qquad x(z)=\frac{y(z)}{1-\lambda^{-1}z}. $$
  3. By Plancherel theorem $y\in\ell^{2+}$ $\Leftrightarrow$ $y(z)\in H^2(\mathbb{T})$ (Hardy space). The function $1/(1-\lambda^{-1}z)\in H^\infty(\mathbb{T})$ due to $\lambda>1$, then $x(z)\in H^2(\mathbb{T})$, so $x\in\ell^{2+}$.

P.S. The whole point here is to say that the stable ($\lambda>1$) linear difference equation is a linear bounded operator on $\ell^{2+}$. There are alternative ways to show that, for example, by using Riesz-Thorin theorem to the convolution for $x_k$ directly (since $1/\lambda^k\in\ell^{1+}$, it is easy to see that the convolution is a linear bounded operator on $\ell^{\infty+}$ and on $\ell^{1+}$, which interpolates it to a linear bounded on $\ell^{2+}$).


Well my solution looks basically the same as that of A.G; perhaps it's a little more elementary. I'll include it since I just spent some time on it!


$$\sum_{k=1}^{\infty}|a_k| < \infty, \sum_{k=1}^{\infty}|b_k|^2 < \infty.$$

Let $f(z) = \sum_{k=1}^{\infty}a_kz^k, g(z) = \sum_{k=1}^{\infty}b_kz^k.$ Then in the open unit disc,

$$f(z)g(z) = \sum_{k=2}^{\infty}\left( \sum_{j=1}^{k}a_jb_{k+1-j}\right) z^k.$$


$$\tag 1 \frac{1}{2\pi }\int_0^{2\pi} |f(re^{it})g(re^{it})|^2 = \sum_{k=2}^{\infty}| \sum_{j=1}^{k}a_jb_{k+1-j} | ^2 r^{2k}.$$

But $|f(re^{it})| \le \sum |a_k| = M,$ so the left side of $(1)$ is $\le M\int_0^{2\pi} |g(re^{it})|^2 \le M \sum |b_k|^2.$ It follows that

$$ \sum_{k=2}^{\infty}|\sum_{j=1}^{k}a_jb_{k+1-j}|^2r^{2k}\le M \sum |b_k|^2$$

for all $r,$ hence

$$\sum_{k=2}^{\infty}| \sum_{j=1}^{k}a_jb_{k+1-j} |^2 \le M \sum |b_k|^2.$$

Now in the problem of the OP, we can take $a_k = 1/\lambda ^k, b_k = y_k.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.